2014
DOI: 10.1002/mame.201300459
|View full text |Cite
|
Sign up to set email alerts
|

Flow Induced Crystallization of Poly(ether‐block‐amide) from the Microinjection Molding Process and its Effect on Mechanical Properties

Abstract: Abstract:Crystallization of Poly(ether-block-amide) during microinjection molding is investigated using polarized light microscopy, atomic force microscopy, small/wide angle X-ray scattering and differential scanning calorimetry. Special morphologies of micro dumbbell parts, such as spherulitic or spherulite-free core structures and unique spherulite structures generated beneath the skin layers, are examined and explained relative to processing conditions. Nanoindentation tests confirm that both the modulus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…When cavity thickness is more than 300µm, the skin area reduces to less than 20% of the entire cross-section, similar to cases where process induced crystallization was studied [21]. Yield stress broadly reduces with an increase of cavity thickness, since the skin ratio decreases, as shown in Figure 19 (b).…”
Section: Mechanical Propertiesmentioning
confidence: 61%
See 4 more Smart Citations
“…When cavity thickness is more than 300µm, the skin area reduces to less than 20% of the entire cross-section, similar to cases where process induced crystallization was studied [21]. Yield stress broadly reduces with an increase of cavity thickness, since the skin ratio decreases, as shown in Figure 19 (b).…”
Section: Mechanical Propertiesmentioning
confidence: 61%
“…Pebax 7233 indicated that the Young's modulus is approximately half that of a standard tensile specimen, strain at break is 30% less than expected from material supplier data sheets, and yield stress is 1.6-2 times higher than standard samples [21]. Such comparison suggests that process induced crystallization and size induced crystallization have a similar level of influence on mechanical properties for microinjection moldings.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations